Seksualitas dan Reproduksi Perempuan dalam Karya-karya Sekar Ayu Asmara - Tineke Hellwig (HISKI, 2008)
The Reformation era has freed the media and public life in general from the tight binding of the New Order era, and enabled the emergence of many women in the realm ofIiterature and culture production. Now, it is not impossible to question the normative standard of the Suharto regime formed by authoritarianism, militarism and monolithic way of thinking. A number of cultural products (literature, theater, film) produced after 1998 focused on urban-cosmopolitan Iife and consumerist life style, and openly brought up issues related with woman sexuality and homophobia, which broke down a bunch of taboos and the common views in the society about heterosexuality, marriage and family values. Even though several woman writers and artists of this time have shown empathy to the celebration of woman sexuality and functioned to break down the